All-Diamond Microfiber Electrodes for Neurochemical Analysis. Issue 12 (1st January 2018) - Rusinek, Cory A.; Guo, Yue; Rechenberg, Robert; Becker, Michael F.; Purcell, Erin; Verber, Matthew; McKinney, Collin; Li, Wen
Abstract : Neurochemical sensing with implantable microelectrodes has created multiple research opportunities in the field of neuroscience. The ability to record extracellular biopotentials and detect neurotransmitters with high sensitivity has enabled deeper understanding of brain and nervous system function. Diamond has many advantages over other electrode materials such as good biocompatibility, wide potential window, low double-layer capacitance, long-term stability, resistance to corrosion/fouling, and fabrication flexibility. In this work, we present a micromachined, implantable, all-diamond microfiber capable of reliable, precise neurochemical sensing. The all-diamond fiber consists of a conductive boron-doped polycrystalline diamond (BDD) core encapsulated in layers of insulating polycrystalline diamond (PCD) cladding. The PCD serves as a biocompatible and hermetic package while also acting as a dielectric barrier to prevent signal cross-talking. The all-diamond microelectrodes were thoroughly characterized using topographical and electrochemical methods. The capability for neurotransmitter sensing was completed using dopamine (DA) as the model analyte. Fast-scan cyclic voltammetry (FSCV) of DA was also completed to demonstrate the practicality for in vivo sensing at rapid rates. The fabrication is described in great detail and the capability for batch-scale process is demonstrated. These novel all-diamond microelectrodes have commercial-scale potential, generating a powerful tool for neurochemical analysis.